Hong Kong Med J 2020
DOI: 10.12809/hkmj198197
|View full text |Cite
|
Sign up to set email alerts
|

Second tier non-invasive prenatal testing in a regional prenatal diagnosis service unit: a retrospective analysis and literature review

Abstract: The Hong Kong Hospital Authority has newly introduced a new Down's syndrome screening algorithm that offers free-of-charge noninvasive prenatal testing (NIPT) to women who screen as high risk. In preparation for this publicfunded second tier NIPT service, the present study was conducted to retrospectively analyse women eligible for NIPT and to review the local literature. Methods: Our retrospective study included women screened as high risk for Down's syndrome (adjusted term risk ≥1:250) during the period of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Local research confirmed pregnant people's preference for NIPT (173). The uptake rate among users with a high-chance first-tier screening result gradually increased, ranging from 20% to 90% (108). Both women and healthcare providers perceived NIPT as beneficial in improving prenatal care.…”
Section: Hong Kongmentioning
confidence: 85%
See 1 more Smart Citation
“…Local research confirmed pregnant people's preference for NIPT (173). The uptake rate among users with a high-chance first-tier screening result gradually increased, ranging from 20% to 90% (108). Both women and healthcare providers perceived NIPT as beneficial in improving prenatal care.…”
Section: Hong Kongmentioning
confidence: 85%
“…They would accept a miscarriage risk of up to 0.5% as a trade-off for obtaining more rather than less information when making a reproductive decision (33). Interestingly, women expressed a decreased interest in NIPT and an increased preference for invasive testing (with a chromosomal microarray for obtaining more definitive genetic results) when they were counseled that the procedure-related fetal loss rate of the invasive test was 0.1-0.2% (34,108).…”
Section: Mainland Chinamentioning
confidence: 99%
“…In 2014, when NIPT remained a self-financed item, 57.8% of women opted for NIPT as a second-tier test after screen positive, compared with 30.4% opting for NIPT as a primary screening test 14 . In 2015-2016, the uptake of NIPT in women with positive DS screening increased to 67%, whereas 31% opted for invasive testing and 2% had no further testing 11 . In 2015-2016, when NIPT was offered free-of-charge under a university research protocol, among 347 women with positive DS screening, 62.2% opted for NIPT and 37% opted for invasive testing with chromosomal microarray 15 .…”
Section: Discussionmentioning
confidence: 99%
“…For invasive testing, quantitative fluorescent polymerase chain reaction (to exclude common aneuploidies) was used, followed by chromosomal microarray and/or karyotyping. The procedure-related miscarriage risk for chorionic villus sampling was 1% and for amniocentesis was 0.1% to 0.5% 6,11,12 . All screen-positive women were offered a detailed morphology scan at 20 weeks to exclude fetal structural abnormalities unless the NIPT or invasive testing already confirmed specific pathology.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation